Anti-hemorrhoidal plants in Iranian traditional medicine - S. Dehdari; H. Hajimehdipoor; S. Esmaeili*; R. Choopani; S.A. Mortazavi (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Hemorrhoidal disease is a prevalent anorectal condition that is explained as the symptomatic expansions and displacements of the normal hemorrhoidal cushions. Symptomatic hemorrhoids affect more than one million individuals in the western world every year. Hemorrhoids is a well-known disease in Iranian traditional medicine (ITM). Avicenna and other Iranian traditional practitioners have exactly defined this condition in their manuscripts and herbal therapy was the main treatment that was recommended. In the present study, medicinal plants with hemorrhoids healing properties in ITM have been investigated. Method: ITM  textbooks including "Al Qanun fi al-tibb (Canon of medicine)", "Al-Havi (Liber continent)", "Alabnie an haghaegh ol advieh (the Book of remedies)", "Al-jami li-mufradat al-adviya va al-aghziya", "Ikhtiyarat‑e‑ badiyee", "Tohfat-ol-momenin" and "Makhzan ol advieh  were searched to find the most used herbs. Results: Some of obtained plants such as Commiphora mukul (Hook. ex Stocks) Engl., Phyllantus emblica L. and Aloe vera (L.) Burm.f.,were the most used herbs. Conclusion: these plants could be introduced as the good resources for future studies in order to produce novel drugs.